Impact of Ramadan Intermittent Fasting on Salivary pH, Flow Rate, and Electrolyte Levels in Healthy Adult Men - Sinda Yacoub; Mehdi Khemiss; Amira Besbes; Helmi Ben Saad (American Journal of Men's Health)
This before-and-after design study, which was conducted during Ramadan 2023, aimed to compare salivary flow rate (SFR), potential hydrogen (pH), and electrolyte concentrations before Ramadan (BR), at the end of Ramadan (ER), and after Ramadan (AR). Men aged 20 to 30 years who were fasting during Ramadan were recruited from the University of Monastir (Tunisia). Unstimulated saliva was collected over a 5-minute period between 10 and 11 a.m. at BR, ER, and AR. After recording the SFR, the pH was measured immediately using a pH meter. Concentrations of several salivary electrolytes (e.g., calcium, potassium, sodium, chloride, and phosphate) were determined using inductively coupled plasma-optical emission spectroscopy. Twenty-seven participants completed all three sessions. Ramadan intermittent fasting (RIF) caused significant changes only in calcium levels and pH. The mean (M) ± standard deviation (SD) salivary calcium concentration decreased during ER compared to BR and AR (0.10 ± 0.08 vs. 0.21 ± 0.18 [ p = .041] vs. 0.22 ± 0.20 [ p = .026], respectively). The M ± SD salivary pH increased during ER compared to BR (6.88 ± 0.23 vs. 6.69 ± 0.35 [ p = .049], respectively). To conclude, RIF decreased salivary calcium, increased salivary pH, and did not significantly affect potassium, sodium, chloride, or phosphate. The pH change, although statistically significant, was clinically insignificant, as values remained normal. The lack of reference values for salivary calcium limits assessment of its clinical impact. There is a need for further research on the effects of RIF on saliva secretion.